Process variables optimization for preparation and characterization of novel adsorbent from lignocellulosic waste - Chowdhury, Z.Z.; Khalid, K.; Arami-Niya, A.; Khan, R.A.; Zain, Sharifuddin Md (2012)
In this study, powdered activated carbon (PAC) was produced from agricultural waste biomass of kenaf (Hibiscus cannabinus L.) core or stalk, and the process variables were optimized by applying central composite design (CCD). The influences of carbonization temperature, duration of activation, and impregnation ratio on removal percentage of copper Cu(II) ions from aqueous solution and carbon yield were investigated. A quadratic model for adsorption percentage and a 2FI model for carbon yield were developed. The models were used to determine optimum process variables for production of activated carbon from the woody core of kenaf. From the analysis of variance (ANOVA), the most significant factor on each response of adsorption capacity and yield were identified. An activation temperature of (568±1)°C, activation time of 2.02 hours, and impregnation ratio of 1.75 were found as optimum production conditions. The experimental results showed excellent agreement with the predicted results obtained from a designed experiment that included the variables and responses of sorption capacity and yield. Textural properties of the prepared activated carbons were determined. The performance of the prepared activated carbon was further evaluated by fitting the equilibrium data with regression equations of Langmuir, Freundlich, and Temkin models at different temperatures. The research concluded that the prepared sorbent has good potential to remove Cu (II) ions from waste water.